Effects of Auditor’s Independence and Rotation on the Quality of Audit in Sierra Leone - Lamin Kaira; Abdul Conteh; Zulfikar Zulfikar (Ridwan Institute, 2023)
As Sierra Leone attempts to recover from the past excruciating economic downturn, it is essential to preserve investors' faith in the capital market by conducting excellent audits and providing truthful financial reporting. However, it is unclear how auditor independence, rotation, and audit quality relate to one another in Sierra Leone. In Sierra Leone, the relationship between independence, rotation, and audit quality will be thoroughly and in-depth examined in this study. The study’s main objective is to know the effects of auditor independence and rotation on the quality of audits in Sierra Leone. Its specific objectives are the effects of auditor rotation on the quality of audits, the reasons behind the lack of auditor independence in Sierra Leone, the relationship between auditors’ independence and Audit Quality, and the reasons for the voluntary rotation of auditors in Sierra Leone. The respondents of the research were auditors in the audit services in Sierra Leone. And the data were analyzed using SPSS. The research results show that auditor rotation is perceived to enhance audit quality, and there is a significant link between auditors' independence and audit quality. The lack of auditor independence in Sierra Leone is primarily due to their financial interests in clients' companies, resulting in conflicts of interest additionally, the absence of a code of ethics and the voluntary nature of auditor rotation contribute to the lack of independence. The study emphasizes the crucial role of auditor competence and independence in ensuring audit quality. It re recommended that Auditor rotation be implemented in Sierra Leone to improve auditor independence, enhance the quality of audits, and establish and provide a comprehensive code of ethics for auditors in Sierra Leone.